IMPLEMENTASI KURIKULUM ISMUBA DALAM MENINGKATKAN KETERAMPILAN, SIKAP DAN PENGETAHUAN SISWA DI SD MUHAMMADIYAH SLANGGEN - Faizah Ayu Yuniarti; Hafidh Nur Fauzi; Hendro Widodo (Khazanah Pendidikan, 2020)
ABSTRACTThe implementation of the Al-Islam curriculum, Kemuhammadiyahan and Arabic(ISMUBA) has very different characteristics from the general curriculum. there are stillmany obstacles that are found that greatly affect learning outcomes both learning mediaand assessment that are more complicated. then the method used in learning has notbeen effective and in accordance with learning material. This research method is amethod of classroom action research conducted in improving the learning process, withfour meetings. The assessment taken in this study is an evaluation of the evaluation ofeach meeting in the form of attitudinal value, knowledge value and skill value guided bythe teacher's book in chapter three "Purify" at the attitude value the emergence of anattitude of confidence, curiosity and independence Already cultured by 20.68% attitudeconfidence, and curiosity while being independent 6.2% lower because students stillhaven't familiar with the application of the Al-Islam, Kemuhammadiyahan and Arabiclanguages curriculum. The results of student knowledge are seen in developments Verygood value at 1st meeting was 36.4%, in the second meeting it decreased to 30.3%, whileat the third meeting there was a return of 52.25%. Whereas in the results of the student'sskills four meetings appear at each meeting in the very good category at the first meetingat 18.1%, at the second meeting increased to 27.3%, the third meeting decreased to asbig as 20.68%, while the fourth meeting increased again by 65.62%..Keywords: Curriculum ISMUBA, skill, attitudes, knowledge